2021
DOI: 10.1002/ange.202109682
|View full text |Cite
|
Sign up to set email alerts
|

Designing Anion‐Type Water‐Free Zn2+ Solvation Structure for Robust Zn Metal Anode

Abstract: Rechargeable aqueous Zn batteries are potential for large‐scale electrochemical energy storage due to their low cost and high security. However, Zn metal anode suffers from the dendritic growth and interfacial hydrogen evolution reaction (HER), resulting in the deterioration of electrode/battery performance. Here we propose that both dendrites and HER are related to the water participated Zn2+ solvation structure‐Zn(H2O)62+ and thus can be resolved by transforming Zn(H2O)62+ to an anion‐type water‐free solvati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 41 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…1e ), which confirm the coexistence of Zn 2+ -O and Zn 2+ -N coordination in ZnSO 4 -C 3 N 4 QDs system, with bond lengths of 2.05 Å and 3.35 Å, respectively. The Zn 2+ -O pair in ZnSO 4 -C 3 N 4 QDs is slightly enlarged compared with that in ZnSO 4 (~1.94 Å) 22 , 35 , in accordance with the above XANES results. The weakened bonding strength between Zn 2+ and H 2 O reduces the proton activity and suppresses electrochemical water decomposition, as also evidenced by a gradually lower hydrogen evolution potential with increasing doses of C 3 N 4 QDs in the electrolyte (Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…1e ), which confirm the coexistence of Zn 2+ -O and Zn 2+ -N coordination in ZnSO 4 -C 3 N 4 QDs system, with bond lengths of 2.05 Å and 3.35 Å, respectively. The Zn 2+ -O pair in ZnSO 4 -C 3 N 4 QDs is slightly enlarged compared with that in ZnSO 4 (~1.94 Å) 22 , 35 , in accordance with the above XANES results. The weakened bonding strength between Zn 2+ and H 2 O reduces the proton activity and suppresses electrochemical water decomposition, as also evidenced by a gradually lower hydrogen evolution potential with increasing doses of C 3 N 4 QDs in the electrolyte (Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…In addition, the chloride salt with bulky cation (1-ethyl-3-methylimidazolium chloride, EMImCl) electrolytes was utilized to unlock the cation–water interaction, 211 release the bound water in [Zn(H 2 O) 6 ] 2+ , and form ZnCl 4 2− as an anion-type solvation structure in the electrolyte. As a result, the regulation of solvation structures significantly prevented the dendrite growth and other side reactions (Fig.…”
Section: A Summary Of Solvation Structure Regulation Strategiesmentioning
confidence: 99%
“…8h, this anion-type water-free Zn 2+ solvation structure electrolyte (ASE) presented a lower energy in the X-ray absorption near-edge structure (XANES) spectrum when compared with the pure ZnSO 4 electrolyte, demonstrating that the local structures of Zn 2+ ions were changed, and this new solvation structure in ASE donated more electrons to Zn 2+ and thus lowered the valence of Zn 2+ . 211 Furthermore, the Fourier transformation of the extended X-ray absorption fine structure (EXAFS) spectra of the ZnSO 4 electrolyte and ASE was conducted (Fig. 8i), a higher shift in the k space of ASE than that of the ZnSO 4 electrolyte was observed, indicated that Cl − squeezed out H 2 O and involved in the Zn 2+ coordination shell after introducing EMImCl into the ZnSO 4 electrolyte.…”
Section: A Summary Of Solvation Structure Regulation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations